2007
DOI: 10.1038/nature05975
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy acoustic plasmons at metal surfaces

Abstract: Nearly two-dimensional (2D) metallic systems formed in charge inversion layers and artificial layered materials permit the existence of low-energy collective excitations, called 2D plasmons, which are not found in a three-dimensional (3D) metal. These excitations have caused considerable interest because their low energy allows them to participate in many dynamical processes involving electrons and phonons, and because they might mediate the formation of Cooper pairs in high-transition-temperature superconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
174
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 23 publications
11
174
1
1
Order By: Relevance
“…the regions where bulk electrons (3D electron gas) attempt to screen the charge disbalance in the 2D system. The observation of this mode by EELS was first reported for the Be(0001) surface [51] and later for Au(111) [53] and Cu(111) surfaces [54].…”
Section: Fundamental Properties Of Plasmons Probed By Electron Energymentioning
confidence: 99%
“…the regions where bulk electrons (3D electron gas) attempt to screen the charge disbalance in the 2D system. The observation of this mode by EELS was first reported for the Be(0001) surface [51] and later for Au(111) [53] and Cu(111) surfaces [54].…”
Section: Fundamental Properties Of Plasmons Probed By Electron Energymentioning
confidence: 99%
“…It is therefore crucial for structure and array formation, as also demonstrated below. This scenario is very different from the formation of 2D acoustic surface plasmons generated by partially filled surface states of bulk metals, 13,14 where the response of the bulk metal electrons has to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The depth penetration of a surface state depends upon how far it is removed from closest bulk band edge [11]. Moreover, it has been reported that the interplay between the surface electronic states and the bulk electronic states in the same region of the space (near the surface) could result in acoustic surface plasmon due to charge oscillation between the 2D and 3D subsystems [15].…”
Section: Introductionmentioning
confidence: 99%